Effects of the Aerobic Exercise Program with Music on the Body Composition and Subcutaneous Fat of Young Women: A Systematic Review - Miljan Hadzovic; Ana Lilic; Nikola Prvulovic; Predrag Ilic; Mima Stankovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
Numerous authors recommend participation in various types of aerobic exercise, pointing out their positive effects both in terms of the prevention of various illnesses, and in the improvement of one's health status. The increasingly popular group fitness programs, as preprogrammed forms of physical exercise to music, have positive effects on body composition among women, such as a decrease in body mass and fat, and thus lead to an improvement in overall physical appearance. The aim of this research was to determine the effects of aerobic exercise to music on body composition and subcutaneous fat among young women. In order to compile data from existing research on the effects of aerobic exercise on young women, the following electronic databases were searched: PubMed, SCIndeks, PEDro, J-GATE, DOAJ and Google Scholar. The systematic review was undertaken in accordance with the statement of Preferred Reports for Systematic Review and Meta-Analyses (PRISMA). Papers dating from 2006 to 2019 were analyzed. The research results confirm the positive influence of aerobic exercise to music on the parameters of body composition and subcutaneous fat among young women, irrespective of the overall duration of the exercise programs, with the conclusion that programs lasting up to 12 weeks are more effective when it comes to the decrease and maintenance of body weight, fat reduction, increase in muscle tissue, and lead to an improvement in aerobic abilities. The best effects of this type of exercise at an intensity level of 50 to 80% of maximum heart rate are primarily achieved among obese and overweight individuals.